Biofortifikasi Untuk Peningkatan Keragaman Populasi Dasar Padi Gogo Beras Khusus - Yullianida, Yullianida; Hermanasari, Rini; Lestari, Angelita Puji; Hairmansis, Aris (Universitas Musamus, Merauke, Papua, 2021)
Biofortification is a process of increasing the nutritional content of agricultural commodities to meet the preferences of consumers who in recent years have begun to tend to have a healthy lifestyle. Specialty rice can include aromatic rice, sticky rice, pigmented rice and nutritious rice (rice containing zinc, iron or high anthocyanin). The limited superior varieties of upland rice causes the need to increase genetic diversity through the formation of based populations with conventional crossing. The hybridization block and F1 planting were conducted at MT 1 2019 in Muara Experimental Station-ICRR, Bogor. Crossing parents consist of advanced lines, introduced lines, local varieties and national varieties. Development of upland rice based population in MT 1 2019 resulted 64 crossbreeding combinations and 41 crossbreeding combinations among them aimed at obtaining special quality upland rice consisting of 24 single crosses, eight back crosses, seven top crosses and two double crosses. Whereas for F1 planting, upland rice for MT 1 2019 consisted of 129 numbers and 53 of them aimed at good quality rice. Of the 53 F1 numbers, 42 numbers were selected, which continued to become the bastar population (F2) in MT 2 2019 with the modification-bulk selection method.